2019
DOI: 10.5603/ep.a2019.0041
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine diseases as causes of secondary hyperlipidemia

Abstract: Cardiovascular diseases are among the leading causes of increased morbidity and mortality in developed and developing countries. One of the most important risk factors responsible for atherosclerosis and subsequent cardiovascular diseases is hyperlipidaemia. Currently, hyperlipidaemias are divided into several clinical entities. The greatest risk is associated with hypercholesterolaemia. As a result, modern guidelines for the treatment and prevention of atherosclerosis focus predominantly on the reduction of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 68 publications
(73 reference statements)
0
16
0
Order By: Relevance
“…Based on the results obtained in the current study, endocrine resistance (hsa01522), AGE-RAGE signaling pathway in diabetic complications (hsa04933) and p53 signaling pathway (hsa04115) might be the main signaling pathways of AM in the treatment of acquired hyperlipidemia. Endocrine diseases have been highlighted as a fundamental cause of acquired hyperlipidemia [ 26 ]. It was found that active compounds in AM might mediate pancreatic β-cell metabolism, thereby improving insulin secretion [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results obtained in the current study, endocrine resistance (hsa01522), AGE-RAGE signaling pathway in diabetic complications (hsa04933) and p53 signaling pathway (hsa04115) might be the main signaling pathways of AM in the treatment of acquired hyperlipidemia. Endocrine diseases have been highlighted as a fundamental cause of acquired hyperlipidemia [ 26 ]. It was found that active compounds in AM might mediate pancreatic β-cell metabolism, thereby improving insulin secretion [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid function has an important impact on lipid profile. Hypothyroidism is one of the common causes of secondary hyperlipidemias [ 135 ]. Elevated TSH level leads to increased expression of PCSK9 [ 136 ].…”
Section: Pcsk9 and The Endocrine Systemmentioning
confidence: 99%
“…Diabetes, a severe disease, also increases the risk of other conditions such as cardiovascular or chronic kidney diseases, causes disabilities such as blindness or lower limb amputation, reduces life expectancy, and poses a burden on health systems and social services [9][10][11][12]. Therefore, it is crucial to identify all risk factors for diabetes, because their modification could reduce morbidity or alleviate the course of this disease.…”
Section: Introductionmentioning
confidence: 99%